1996
DOI: 10.1111/j.1600-0404.1996.tb00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, trauma, and ALS: a case-control study

Abstract: Severe head, neck, and back injury and frequency of sweating both in work and leisure activity showed a strong association with ALS. Further study could test narrower and less common exposures with greater statistical power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 12 publications
(6 reference statements)
4
62
2
Order By: Relevance
“…Our results are in keeping with preceding reports showing no relation between smoking and ALS [13,20,28], in contrast with others [1,7,8,10,11,17,19,21,22,26,27,[30][31][32][33][34]. The causal relationship between smoking and the risk of ALS in the aforementioned studies is actually rather unclear, with increasing risk found alternatively in former smokers [19], in current smokers [11,26,31,34] and in women only [34].…”
Section: Discussioncontrasting
confidence: 59%
“…Our results are in keeping with preceding reports showing no relation between smoking and ALS [13,20,28], in contrast with others [1,7,8,10,11,17,19,21,22,26,27,[30][31][32][33][34]. The causal relationship between smoking and the risk of ALS in the aforementioned studies is actually rather unclear, with increasing risk found alternatively in former smokers [19], in current smokers [11,26,31,34] and in women only [34].…”
Section: Discussioncontrasting
confidence: 59%
“…Although there is some debate about the value of exercise in ALS, as well as whether regular exercise throughout one's lifetime is a risk factor for ALS in humans, 9,32,37,42,46 we believed that endurance training might increase antioxidant enzyme capacity 20,21,38 and mitochondrial capacity 17 or induce regular release of neurotrophic factors from muscle, 12,13,28,48,53 which would ultimately protect spinal motor neurons or skeletal muscles in the G93A mouse. However, our results showed that high-intensity endurance exercise training had no effect on disease onset in male and female mice and decreased survival by 11 days in male mice only.…”
Section: Discussionmentioning
confidence: 98%
“…Although it was suggested the regular exercise may be beneficial as treatment during the early 9 and late 37 stages of the disease, others have hypothesized that lifelong, habitual heavy exercise may be a risk factor for developing ALS in humans. 32,42,46 However, endurance exercise training is known to induce cellular adaptations in both skeletal muscle and brain that may be beneficial to patients with ALS. In skeletal muscle, endurance training increases the capacity of the major antioxidant enzymes, 20,21,38 reduces oxidative stress following an acute bout of exercise 35 and increases resistance to oxidative stress in aged rats.…”
mentioning
confidence: 99%
“…Some studies have suggested that a family history of ALS and other neurodegenerative diseases, such as Alzheimer's disease (AD) and Parkinson's disease (PD), is an important factor in the development of ALS [1][2][3][4][5][6]. Many other epidemiologic investigations have focused on the risk associated with traumatic events, such as skeletal fractures [1][2][3][4][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], electrical shocks [2,4,10,12,16,18], and surgeries [1-4, 8-10, 13, 14, 18, 19], but with conflicting results. Researchers have also examined the relation of several other factors to ALS including residential history, specifically pertaining to rural residence [3,14,18,19,21,23,25], a history of travel to the areas of the western Pacific where ALS is considered endemic, such as Guam, New Guinea, and the Kii peninsula of Japan [2,10,…”
Section: Introductionmentioning
confidence: 99%